Single Nucleotide Polymorphisms in Starch Biosynthetic Genes Associated With Increased Resistant Starch Concentration in Rice Mutant - Gurunathan, Selvakumar; Ramadoss, Bharathi Raja; Mudili, Venkataramana; Siddaiah, Chandranayaka; Kalagatur, Naveen Kumar; Bapu, Jutti Rajendran Kannan; Mohan, Chakrabhavi Dhananjaya; Alqarawi, Abdulaziz A.; Hashem, Abeer; Abd_Allah, Elsayed Fathi (Frontiers in Genetics, 2019)
Abstract Resistant Starch (RS), plays a crucial role in human health and nutrition by controlling glucose metabolism. RS or dietary fibre content in rice is low because it goes through a variety of process before it is ready for cooking and consumption. Hence, this study was carried out to develop a rice mutant with increased RS. The rice mutant (γ278) with increased RS was developed by utilizing gamma (γ) rays as a mutagen. Mutant γ278 was characterized for mutations in the starch biosynthetic genes viz., GBSSI, SSI, SSIIa, SSIIIa, SBEIa and SBEIIb to reveal the functional mutations/variations led to high RS content in rice. A total of 31 sequence variants/mutations in six genes were identified. We report the discovery of three deleterious mutation/variants each in GBSSI, SSIIa, and SSIIIa with the potential to increase RS content in rice. Further, wild x mutant crosses were made to develop an F2 population to study the effect of combination of deleterious mutations. The SNP (GBSSI:ssIIa:ssIIIa) combination responsible for high RS content in F2 population was identified and recorded highest amylose content (AC) (26.18%) and RS (8.68%) content. In conclusion, this marker combination will be highly useful to develop a rice variety with increased RS.